2017
DOI: 10.1007/s12022-017-9475-6
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Treatment of Metastases to the Thyroid Gland: a Meta-Analysis

Abstract: The thyroid is a rare site of clinically detectable tumor metastases; even though the gland is a highly vascularized structure, the frequency of metastases in the routine practice is less than 0.2% of all thyroid malignancies. The purpose of our meta-analysis is to evaluate the frequency of metastatic diffusion from other primary tumors to the thyroid gland and to suggest the best possible treatment through an evidence-based study. Relevant studies were identified by searching the following databases: PubMed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
65
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(65 citation statements)
references
References 53 publications
0
65
0
Order By: Relevance
“…Patients with secondary carcinoma of the thyroid from a lung primary have a particularly poor prognosis with most patients dying within months of metastatic disease. [27][28][29]58,59…”
Section: Discussionmentioning
confidence: 99%
“…Patients with secondary carcinoma of the thyroid from a lung primary have a particularly poor prognosis with most patients dying within months of metastatic disease. [27][28][29]58,59…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature, it represents the first and most useful diagnostic tool in the evaluation of several body lesions. In fact, among the others, it has demonstrated interesting results in terms of diagnostic accuracy in head and neck cancer, breast carcinoma, and cervical carcinoma . To date, only 2 studies, from the same institution, have been published on the diagnostic utility of ultrasound with guided FNAC in the assessment metastatic lymph node disease in vulvar carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, among the others, it has demonstrated interesting results in terms of diagnostic accuracy in head and neck cancer, breast carcinoma, and cervical carcinoma. [10][11][12][13][14] To date, only 2 studies, from the same institution, have been published on the diagnostic utility of ultrasound with guided FNAC in the assessment metastatic lymph node disease in vulvar carcinoma. Moskovic et al, in their pilot study on 21 patients with early vulvar carcinoma using ultrasound and FNAC, confirmed an overall sensitivity of 83% and specificity of 82% for the detection of groin lymph node metastases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations